Essential oil extraction pink pepper (Schinus terebinthifolius Raddi) and determination of cytotoxicity and inhibitory count minimum (Research, Society and Development, 2020)
The essential oil extracted from the fruits of pink pepper (Schinus terebinthifolius Raddi) has antioxidant, antimicrobial and antifungal properties. These properties are related to the presence of antibacterial compounds in its composition. Such compounds can be used to combat deteriorating and pathogenic bacteria in food. Thus, the objective of this study was to extract the essential oil from pink pepper (Schinus terebinthifolius Raddi) and determine the cytotoxicity and minimum inhibitory concentration, in order to investigate its antimicrobial effect against bacterial strains, aiming at the possible use of essential oil as a condiment in foods. The essential oil was extracted using a modified Clevenger apparatus (hydrodistillation) and the parameters of appearance, odor, color and density were determined. For cytotoxicity, eight concentrations (500; 250; 150; 50; 25; 12.5; 6.24 and 0 µg / ml) of the essential oil applied in Artemia salina were used and for the determination of the minimum inhibitory concentration, eight concentrations were tested (0; 0.01625; 0.0325; 0.065; 0.125; 0.25; 0.5 and 1%) in five different bacterial strains, two Gram-positive (Staphylococcus aureus ATCC 25923 and Listeria monocytogenes ATCC 19117) and three Gram-negative (Escherichia coli ATCC 25922, Salmonella Typhimurium ATCC 14028 and Salmonella Enteretidis ATCC 13076). The results showed that the cytotoxic concentration was 86.2 µg / ml and the rate of inhibition only for the strain of Staphylococcus aureus was 0.5% and the other strains were not inhibited. Thus, it can be concluded that the essential oil of pink pepper (Schinus terebinthifolius Raddi) can be incorporated into foods to inhibit the strain of Staphylococcus aureus, at a concentration of 0.5%.